A genomic approach for the identification of population management units for the dolphinfish (Coryphaena hippurus) in the eastern Pacific - Mar-Silva, Adan Fernando; Díaz-Jaimes, Píndaro; Ochoa-Zavala, Maried; Ortega-Garcia, Sofia; Sotil, Giovanna; Alegre, Ana; Escarabay, Teddy; Elias, Esteban; Carvajal-Rodríguez, Jose Miguel (Frontiers in Marine Science, 2024)
The population genetic structure of the dolphinfish Corypahena hippurus in the eastern Pacific was investigated to identify possible management units for conservation purposes based on two SNPs datasets of 3867 and 3220 SNPs for young of the year (YOY) and adult individuals, respectively, obtained through NGS protocols. Sampling covered the species’ range distribution in the Tropical Eastern Pacific and was structured into YOY and adult individuals in order to discard the effects of migrating individuals into sampled locations. Our results imply slight but significant differences among locations occupying the latitudinal limits of the species distribution at transitional areas between tropical and subtropical waters. These areas are characterized by strong seasonal variations in sea surface temperature and limit the prevalence of populations in these extremes. Genetic differences also seem to be related to spatial separation of locations, therefore the northernmost (Los Cabos) and southernmost (Peru) locations including a set of oceanic samples, showed the highest levels of genetic differentiation. Whereas were detected barriers to gene flow among spatially separated locations for YOY individuals probably related to site fidelity, manifest limitations to gene flow between Mexico and Central America locations were observed clearly related to oceanic circulation in the area. Design management strategies in countries where the dolphinfish is explored is of primary interest to preserve genetic resources. Therefore, is necessary the correct genetic population delimitation for species that are highly dependent on environmental factors that determine its distributional range as is the case of the dolphinfish.